NILAI-NILAI PENDIDIKAN DALAM KISAH PEWAYANGAN DEWA RUCI - Amrih Tuti Lestari; Betty Mauli Rosa Bustam (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2022)
Wayang kulit is part of the form of local Indonesian culture, which has existed and survived since the time of the ancestors. Puppet shows are not only intended for entertainment, but also contain noble values ​​that can be realized in every aspect of life in the world. The art of wayang kulit has developed as a means of inculcating the value of life which is quite effective in achieving educational goals. In this day and age, there are many educational problems in Indonesia, including the education system that is not good, the quality of education is not evenly distributed, the facilities and infrastructure are very worrying, the quality of education personnel (teachers) is not paid attention to, the curriculum is always patchy. In the wayang purwa story, Dewa Ruci's play has something to do with educational values ​​that can be applied today, which tells of the obedience of a student named Raden Wijasena, who is very persistent in seeking knowledge. The purpose of this study is to describe the educational values ​​contained in the Dewa Ruci puppet story. The story can be used as a contribution to education in Indonesia. The method used is literature study. Through this method, the problems contained in this paper can be solved. The educational values ​​contained in the play include: the importance of the value of perseverance, tenacity, belief and trust in one's choice of knowledge (art), professions, educational interventions and teachers are only facilitators and means in achieving educational goals.